The identity of shield bugs described by Francis Walker from Taiwan (Hemiptera: Heteroptera: Pentatomidae) - Tsai, Jing-Fu; Rédei, Dávid (Zootaxa, 2009)
Francis Walker (1809–1874), an English entomologist, described five species of shield bugs (Hemiptera: Heteroptera: Pentatomidae) from „Formosa” (= Taiwan) in 1868. Four of them have never been recorded again since the original description and their identity has remained unknown so far. Based on the type material deposited at the Museum of Victoria, Abbotsford, Australia, Walker’s species are documented and their identities are clarified. The following new synonymies are proposed: Eysarcorini: Eysarcoris guttigerus (Thunberg, 1783) = E. latus Walker, 1868, syn. n. = E. pustulatus Walker, 1868, syn. n.; Menidini: Menida (Menida) versicolor (Gmelin, 1790) = Rhaphigaster quinquemaculatus Walker, 1868, syn. n.; Myrocheini: Laprius gastricus (Thunberg, 1822) = Sciocoris lugubris Walker, 1868, syn. n. Lectotypes are designated for Eysarcoris latus, E. pustulatus, and Sciocoris lugubris.